Kesulitan Dalam Komunikasi Sesama Siswa di Sekolah Dasar Ketika Menggunakan Bahasa Daerah - Nadiah, Leni; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
Regional languages are an important part of the cultural heritage of a region or country. This study aims to find out how students in elementary school communicate with each other using regional languages. The method used is literature study. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials. There are several impacts of lack of understanding of regional languages, namely: difficulty in understanding learning material, difficulty in communicating. So the way to do this is to include regional languages as subjects in elementary schools and use regional languages as the language of instruction in learning. This is very important to improve students' language and communication skills.